VARIABEL-VARIABEL YANG MEMPENGARUHI KEBIJAKAN HUTANG - RIKI SANJAYA (Jurnal Bisnis dan Akuntansi, 2014)
The objectives of this research is to test and analyze whether firm size, profitability, firm growth, tangibility, institutional ownership, free cash flow, firm age and carbon credit have influence to debt policy. This study was also to find something new which seldom to do with researchers in Indonesian about carbon credit and improve consistency of results from prior researchers. Sample in this research are manufacturing companies with industry classification basic industry and chemicals, which are listed on December 2012 in Indonesia Stock Exchange at 2012. Only 55 companies meet the criterias and taken as samples. The result of this research show that tangibility and free cash flow influence debt policy. While, firm size, profitability, firm growth, institutional ownership, firm age and carbon credit not influence debt policy.